2017
DOI: 10.2174/1874312901711010010
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Autoantibodies in Patients with Primary and Secondary Sjogren’s Syndrome

Abstract: Background: Antibodies to salivary gland protein 1 (SP1), carbonic anhydrase 6 (CA6) and parotid secretory protein (PSP) were discovered in an animal model of Sjogren’s syndrome (SS). Their expression was noted in patients with SS, especially those with lower focus scores on lip biopsies and those with early disease lacking antibodies to Ro and La.Objective: The current studies evaluated these autoantibodies in patients with long-standing SS expressing high levels of anti-Ro antibodies and in patients with Sjo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 16 publications
(18 reference statements)
1
18
0
Order By: Relevance
“…These findings suggest that the novel biomarkers, particularly anti-SP-1 and anti-PSP, are less likely to be detected in advanced primary SS. The same authors also reported that antibodies to SP-1, CA-6, and PSP were more sensitive and specific than anti-SS-A/Ro in patients with SS in conjunction with other autoimmune diseases, which might have been an indication of earlier stage SS in these patients [62].…”
Section: Novel Biomarkers For Ssmentioning
confidence: 85%
See 1 more Smart Citation
“…These findings suggest that the novel biomarkers, particularly anti-SP-1 and anti-PSP, are less likely to be detected in advanced primary SS. The same authors also reported that antibodies to SP-1, CA-6, and PSP were more sensitive and specific than anti-SS-A/Ro in patients with SS in conjunction with other autoimmune diseases, which might have been an indication of earlier stage SS in these patients [62].…”
Section: Novel Biomarkers For Ssmentioning
confidence: 85%
“…In a study using sera from the sicca cohort, anti-SS-A and anti-SS-B positivity identified patients with more severe (or longer duration disease) SS than anti-SP-1, anti-CA-6, and anti-PSP [59]. A recent study in 37 patients with long-standing SS and high anti-SS-A/Ro titer found anti-CA-6 antibodies in 38% of patients but low positivity for antibodies to SP-1 or PSP [62]. These findings suggest that the novel biomarkers, particularly anti-SP-1 and anti-PSP, are less likely to be detected in advanced primary SS.…”
Section: Novel Biomarkers For Ssmentioning
confidence: 96%
“…Detection of circulating antinuclear autoantibodies are identified in the sera of patients [ 45 ]. Studies in animal models and humans with SS demonstrate that SP-1, CA6, and PSP autoantibodies are expressed earlier in patients with lower scores in MGS biopsies [ 46 48 ]. These autoantibodies concentration became higher at the time of diagnosis [ 45 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…These autoantibodies do not allow distinguishing SLE from secondary SS. However, the described study was limited by a small group of SLE patients [52]. In the literature, some cases have been reported of patients with severe symptoms of eye or mouth dryness, in which there was no SS-A/Ro antibodies, but the presence of anti SP-1 antibody was confirmed [53].…”
Section: Antibodies Recognizing Salivary Gland and Lacrimal Gland Tissuementioning
confidence: 94%
“…In recent years, researchers identified autoantibodies to carbonic anhydrase 6 (anti-CA6 antibodies), anti salivary gland protein 1 (SP-1) and anti-parotid secretory protein (PSP) [51]. These antibodies may emerge before pSS marker antibodies such as SS-A/Ro or SS-B/La and are associated with a minor focus score; these antibodies also occur more often in patients who did not have anti-SS-A/Ro antibodies [52]. Interestingly, in Langhe et al work, anti CA6-IgA antibodies were detected primarily in patients with long pSS duration; other autoantibodies such as anti-CA6, PSP, and SP1 in IgG and IgM class were more frequently observed in SSc and MCTD with secondary SS.…”
Section: Antibodies Recognizing Salivary Gland and Lacrimal Gland Tissuementioning
confidence: 99%